The influence of plant extracts on viability of ST3 and ST7 subtypes of Blastocystis sp. - Karolina Kot; Adam Michaliszyn; Elżbieta Kalisińska; Małgorzata Lepczyńska (Gut Pathogens, 2024)
Abstract Blastocystis sp. is one of the most frequently detected protozoa during stool specimen examination. In the last decade, the studies about the pathogenic potential of Blastocystis sp. have intensified. Additionally, treatment approaches against this parasite are still disputable. The study aimed to investigate the in vitro activity of the substances of natural origin against two subtypes (ST) of Blastocystis sp.—ST3 and ST7. Garlic and turmeric extracts exhibited the highest inhibitory effect in relation to the ST3 viability. While horseradish and turmeric were found to be the most effective extracts to the ST7 viability. The study showed that ginger, garlic, horseradish, and turmeric extracts have potent antimicrobial activity against Blastocystis ST3 and ST7, with the half-maximal inhibitory concentration (IC50) ranging from 3.8 to 4.8 µg/ml and from 3.3 to 72.0 µg/ml, respectively, and thus may be useful in the prevention and control of Blastocystis infections. Additionally, this research confirmed that Blastocystis ST7 is more resistant to the selected plant extracts treatment than Blastocystis ST3 which in consequence may bring some difficulties in its eradication.